Changes associated with Ebola virus adaptation to novel species - Pappalardo, Morena; Reddin, Ian G; Cantoni, Diego; Rossman, Jeremy S; Michaelis, Martin; Wass, Mark N (Bioinformatics (Oxford, England), 2017)
Ebola viruses are not pathogenic but can be adapted to replicate and cause disease in rodents. Here, we used a structural bioinformatics approach to analyze the mutations associated with Ebola virus adaptation to rodents to elucidate the determinants of host-specific Ebola virus pathogenicity. We identified 33 different mutations associated with Ebola virus adaptation to rodents in the proteins GP, NP, L, VP24 and VP35. Only VP24, GP and NP were consistently found mutated in rodent-adapted Ebola virus strains. Fewer than five mutations in these genes seem to be required for the adaptation of Ebola viruses to a new species. The role of mutations in GP and NP is not clear. However, three VP24 mutations located in the protein interface with karyopherin α5 may enable VP24 to inhibit karyopherins and subsequently the host interferon response. Three further VP24 mutations change hydrogen bonding or cause conformational changes. Hence, there is evidence that few mutations including crucial mutations in VP24 enable Ebola virus adaptation to new hosts. Since Reston virus, the only non-human pathogenic Ebolavirus species circulates in pigs in Asia, this raises concerns that few mutations may result in novel human pathogenic Ebolaviruses. m.n.wass@kent.ac.uk , m.michaelis@kent.ac.uk or j.s.rossman@kent.ac.uk. Supplementary data are available at Bioinformatics online.